Specificity of occupational training and occupational mobility : an empirical study based on Lazear's skill-weights approach - Geel, Regula [Verfasser]; Mure, Johannes [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2011)
"According to standard human capital theory, firm-financed training cannot be explained if the skills obtained are general in nature. Nevertheless, in German-speaking countries, firms invest heavily in apprenticeship training although the skills are assumed to be general. In our paper, we study the extent to which apprenticeship training is general at all and how specificity of training may be defined based on Lazear's skill-weights approach. We build occupation-specific skill-weights and find that the more specific the skill portfolio in an occupation, the higher the net costs firms have to bear for these apprenticeship training occupations and, at the same time, the smaller the probability of an occupational change during an employee's entire career. Due to the new definition of occupational specificity, we thus find that apprenticeship training - previously assessed as general training - is very heterogeneous in its specificity." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; Humankapitaltheorie; Berufsausbildung; Berufliche Qualifikation; Spezialisierung; Berufliche Mobilität; Berufsverlauf; Berufswechsel; Ausbildungsinvestition